2021
DOI: 10.3389/fchem.2021.694998
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Therapeutic Interventions: Antimicrobial Peptides and Small Molecules to Treat Microbial Keratitis

Abstract: Microbial keratitis is a leading cause of blindness worldwide and results in unilateral vision loss in an estimated 2 million people per year. Bacteria and fungus are two main etiological agents that cause corneal ulcers. Although antibiotics and antifungals are commonly used to treat corneal infections, a clear trend with increasing resistance to these antimicrobials is emerging at rapid pace. Extensive research has been carried out to determine alternative therapeutic interventions, and antimicrobial peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 248 publications
(281 reference statements)
0
6
0
Order By: Relevance
“…Phage therapy has proven effective against the management of P aeruginosa keratitis, yet its use is strain specific. Additionally, development of antiseptics and antimicrobial peptides are warranted for these recalcitrant pathogens …”
Section: Discussionmentioning
confidence: 99%
“…Phage therapy has proven effective against the management of P aeruginosa keratitis, yet its use is strain specific. Additionally, development of antiseptics and antimicrobial peptides are warranted for these recalcitrant pathogens …”
Section: Discussionmentioning
confidence: 99%
“…aureus and plays a major role in staphylococcal keratitis ( 33 , 34 ). The destruction and lysis of corneal structures induced by bacterial infection increase corneal opacity with the presence of opaque or cloudy area on the cornea ( 35 ). The change in corneal opacity and the measurement of bacterial growth using CFU was determined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with existing antibacterial agents, AMPs have unique mode of action, so they have received special attention as a potential treatment for microbial infections [26] . As numerous studies over the past two decades have shown, human AMPs already play a crucial role in microbial keratitis [11,[15][16][17][24][25][26] .…”
Section: Variable Expression Of Amps Between Fusarium Andmentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are host defense protein peptides secreted naturally by epithelial cells and immune cells, playing an important role in the primitive immune system and adaptive immune system, and having a wide range of activities against pathogens such as viruses, bacteria, and fungi [10][11][12][13] . Several articles have described the presence of AMPs, such as human beta-defensin (HBD) and LL-37 on the surface of the human ocular surface (OS) and their expression in corneal infections [14][15][16][17] . In recent years, a large number of studies have confirmed the antifungal activity of AMPs in animals [18][19][20][21] , in corneal epithelial cells [22][23] and in humans [24][25] .…”
Section: Introductionmentioning
confidence: 99%